2012
DOI: 10.1371/journal.pone.0031923
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Two Numerical Systems That Are Similar in Humans and Guppies

Abstract: BackgroundHumans and non-human animals share an approximate non-verbal system for representing and comparing numerosities that has no upper limit and for which accuracy is dependent on the numerical ratio. Current evidence indicates that the mechanism for keeping track of individual objects can also be used for numerical purposes; if so, its accuracy will be independent of numerical ratio, but its capacity is limited to the number of items that can be tracked, about four. There is, however, growing controversy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
160
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 67 publications
14
160
0
Order By: Relevance
“…An alternative hypothesis to explain the supra-second time estimation impairment in DDs that we observed may be that sub-and supra-second distinctions in the time domain parallel small (up to 3-4) and bigger numerosity (bigger than 4) processing in the numerical domain (Agrillo et al, 2012;Buhusi & Cordes, 2011;Butterworth, 2010;Trick & Pylyshyn, 1993). This suggestion is based on the proposal that smaller numbers rely on similar mechanisms as sub-sec time perception, while bigger numbers rely on joint mechanisms as supra-second time estimation (Buhusi & Cordes, 2011).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…An alternative hypothesis to explain the supra-second time estimation impairment in DDs that we observed may be that sub-and supra-second distinctions in the time domain parallel small (up to 3-4) and bigger numerosity (bigger than 4) processing in the numerical domain (Agrillo et al, 2012;Buhusi & Cordes, 2011;Butterworth, 2010;Trick & Pylyshyn, 1993). This suggestion is based on the proposal that smaller numbers rely on similar mechanisms as sub-sec time perception, while bigger numbers rely on joint mechanisms as supra-second time estimation (Buhusi & Cordes, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…This idea is consistent with the proposition that dyscalculics would be more impaired when bigger numbers are involved (but see But-terworth, 2010), and also with the fact that DDs are not significantly impaired in sub-sec timings (Cappelletti et al, 2011a). Furthermore, the transition between sub-second ('automatic' or 'sensory-motor' timing, Bueti et al, 2012;Buhusi & Meck, 2005;Buonomano, 2007;Lewis & Miall, 2003;Macar et al, 2006;Naatanen et al, 2004;Wiener et al, 2010) and supra-second ('cognitive') timing mechanisms occurs at around 3 s (Gilaie-Dotan et al, 2011;Poppel, 1997), which might parallel the transition between mechanisms supporting small and larger numerosities (Agrillo et al, 2012;Buhusi & Cordes, 2011;Cordes & Brannon, 2009), although there is no consensus about this idea (see Buhusi & Cordes, 2011 for review). While a distinction between 'small' and 'large' numerosities can be dichotomised, one might also consider it on a magnitude continuum.…”
Section: Discussionmentioning
confidence: 99%
“…If the computation supported by human subcortex is related to that performed by other species, one would expect facilitation for both larger and smaller numbers because other nonprimate species do evince ratio-dependent effects for both small and large numbers (38,40,42). In this experiment, participants performed the same task as in experiment 2, but with arrays with small numbers (one to four) of dots.…”
Section: Methodsmentioning
confidence: 96%
“…Several studies have documented ratio effects in the subitizing range (55-59), but others have found ratio effects only with larger numbers (22,42) and the emergence of these effects may be experiment-or task-dependent (54). Our findings corroborate previous research showing that ratio effects exist for numerosities both within and beyond the subitizing range, and, in the context of this particular experimental approach, the subcortex appears to represent ratio-dependent numerosity for the evaluation of both small and large numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation